A close binary lens revealed by the microlensing event Gaia20bof - Bachelet, Etienne; Rota, P.; Bozza, V.; Zieliński, P.; Tsapras, Y.; Hundertmark, M.; Wambsganß, Joachim; Wyrzykowski, Ł.; Mikołajczyk, P. J.; Street, R. A.; Jaimes, R. Figuera; Cassan, A.; et al. (The astronomical journal, 2024)
During the last 25 yr, hundreds of binary stars and planets have been discovered toward the Galactic bulge by microlensing surveys. Thanks to a new generation of large-sky surveys, it is now possible to regularly detect microlensing events across the entire sky. The OMEGA Key Projet at the Las Cumbres Observatory carries out automated follow-up observations of microlensing events alerted by these surveys with the aim of identifying and characterizing exoplanets as well as stellar remnants. In this study, we present the analysis of the binary lens event Gaia20bof. By automatically requesting additional observations, the OMEGA Key Project obtained dense time coverage of an anomaly near the peak of the event, allowing characterization of the lensing system. The observed anomaly in the lightcurve is due to a binary lens. However, several models can explain the observations. Spectroscopic observations indicate that the source is located at ≤2.0 kpc, in agreement with the parallax measurements from Gaia. While the models are currently degenerate, future observations, especially the Gaia astrometric time series as well as high-resolution imaging, will provide extra constraints to distinguish between them.